Selection of the surgical approach for patients with cStage IA lung squamous cell carcinoma: A population-based propensity score matching analysis - Shao, Shengteng; Song, Guisong; Wang, Yuanyong; Yi, Tengfei; Li, Shuo; Chen, Fuhui; Li, Yang; Liu, Xiaotong; Han, Bin; Liu, Yuhong (Frontiers in Oncology, 2022)
Background This study aimed to conduct a comparative analysis of the survival rates after segmentectomy, wedge resection or lobectomy in patients with cStage IA lung squamous cell carcinoma. Methods We enrolled 4,316 patients who had cStage IA lung squamous cell carcinoma (SCC) from the Surveillance, Epidemiology, and End Results (SEER) database. Cox proportional hazards model was conducted to recognize the potential risk factors for overall survival (OS) and lung cancer-specific survival (LCSS). To eliminate potential biases of included patients, propensity score matching (PSM) method was used. OS and LCSS rates were compared among three groups stratified according to tumor size. Results Kaplan-Meier analyses revealed no statistical differences in the rates of OS and LCSS between wedge resection (WR) and segmentectomy (SG) groups for patients who had cStage IA cancers. In patients with tumors ≤1 cm, LCSS favored lobectomy (Lob) compared to segmentectomy, but a similar survival rate was obtained for wedge resection and lobectomy. For patients with tumors sized 1.1 to 2 cm, lobectomy had improved OS and LCSS rates compared to the segmentectomy or wedge resection groups, with the exception of a similar OS rate for lobectomy and segmentectomy. For tumors sized 2.1 to 3 cm, lobectomy had a higher rate of OS or LCSS than wedge resection or segmentectomy, except that lobectomy conferred a similar LCSS rate compared to segmentectomy. Multivariable analyses showed that patients aged ≥75 and tumor sized of >2 to ≤3 cm were potential risk factors for OS and LCSS, while lobectomy and first malignant primary indicator were considered protective factors. The Cox analysis confirmed that male patients aged ≥65 to <75 were independent prognostic factors that are indicative of a worse OS rate. Conclusions The tumor size can influence the surgical procedure recommended for individuals with cStage IA lung squamous cell carcinoma (SCC). For patients with tumors ≤1 cm, lobectomy is the recommended approach, and wedge resection or segmentectomy might be an alternative for those who cannot tolerate lobectomy if adequate surgical margin is achievable and enough nodes are sampled. For tumors ＞1 to ≤3 cm, lobectomy showed better survival outcomes than sublobar resection.